HUBUNGAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJARILMU KEPERAWATAN KOMUNITAS 2 MAHASISWA AKPER BINA SEHAT PPNI KABUPATEN MOJOKERTO - Triwibowo, Heri (JURNAL KEPERAWATAN BINA SEHAT, 2009)
Education of nursing academy is part of high education system of nursing, which produce workable nurse in society so that, the student are given nursing community knowledge. The purpose of research is knowing the relation of learning motivation with the achievement nursing knowledge second community.The method of the research is analytic observational and use crossectional design,sample technique is total sampling.The sample of the reseach is 42 students of Nursing Academy of Bina Sehat PPNI Mojokerto four semester.The research used questionare to measure the motivation while achievement is checked from academic. After all the data’s collected, then analysed by spearman rank correlation test and the level meaning is 0,05 and the result is p = 0,028. It shows that ho = refused. There correlation between studying motivation and achievement nursing second community. The advice is education should optimized the role of academic and for lecture community PJMK need to make the first lecture by inviting the expert of community.Keyword:Studying Motivation,Studying Achievement Nursing Knowledge Of Second Community